ANALYSIS OF COMPETITIVE ADVANTAGE STRATEGY OF BADUY’S WOVEN FABRIC INDUSTRY - Suharyati, Suharyati; Nobelson, Nobelson (Faculty of Economics and Business, Hasanuddin University, 2019)
Abstract: Competition in the business world in Indonesia in the era of globalization is very strict at the national, regional and international levels. The success of SMEs in Indonesia is inseparable from the role of government and SMEs themselves in an effort to develop SME business activities to achieve competitive advantage. This study aims to analyze the differentiation strategy of Baduy’s woven fabrics as an effort to gain competitive advantage and alternative strategies that can be done to obtain a competitive advantage. Primary data is obtained by questionnaires and interviews with craft makers and local governments through the Department of Industry and Trade / SMI and the SME office. Secondary data is obtained from the Department of Industry and Trade. The technical data analysis used is descriptive quantitative method, through analysis of internal and external factors, SWOT analysis of matrix, space matrix and IE matrix. The results of the analysis using the SWOT matrix are obtained industrial position in an aggressive strategy alternative, by aggressive expansion and promotion. In Internal External Matrix (IE Matrix), results obtained from the position of the Baduy’s weaving industry are in quadrant V (five) with alternative concentration strategies through horizontal integration or stability strategies. SPACE Analysis matrix produces a position in quadrant I (one) with an aggressive strategy alternative. This research model is expected to be an input for the Lebak Regional Government for strategic alternatives in obtaining competitive advantages so that it can help increase the productivity of the Baduy tribe, and be able to contribute or add value in the family even in the regional economy. The research output is a strategy model of competitive advantage in the Baduy’s weaving industry. Keywords: Analysis of external and internal factors, SWOT matrix, Space matrix and IE Matrix, Competitive advantage